Cognitive and physical development in HIV‐positive children in South Africa and Malawi: A community‐based follow‐up comparison study. (19th October 2017) - Sherr, L.; Hensels, I. S.; Tomlinson, M.; Skeen, S.; Macedo, A.
Abstract: Background: Child development is negatively impacted by HIV with children that are infected and affected by HIV performing worse than their peers in cognitive assessments. Methods: We conducted a descriptive follow‐up comparison study ( n =989) in South Africa and Malawi. We tracked child development in 135 HIV‐positive children compared to 854 uninfected children aged 4–13 years attending community‐based organizations at baseline and again 12–15 months later. Results: Children with HIV were more often stunted (58.8% vs. 27.4%) and underweight (18.7% vs. 7.1%). They also had significantly poorer general physical functioning ( M =93.37 vs. M =97.00). HIV‐positive children scored significantly lower on digit span and the draw‐a‐person task. Conclusions: These data clearly show that HIV infection poses a serious risk for child development and that there is a need for scaled up interventions. Community‐based services may be ideally placed to accommodate such provision and deliver urgently needed support to these children.